Association of the TTN, PDK4, and RNF207 mutations with dilated cardiomyopathy in Dobermanns from the United Kingdom - Luke C. Dutton; Andrew Crosland; Joanna Dukes-McEwan; David J. Connolly (PLoS ONE, 2025)
A missense mutation in the titin gene (TTN) and a splice-site mutation in the pyruvate dehydrogenase kinase 4 gene (PDK4) have been associated with dilated cardiomyopathy (DCM) in Dobermanns from the United States. Additionally, a missense mutation in the gene RNF207 has been reported in association with DCM from a European Dobermann cohort. Based on this we examined the association of these variants with DCM in United Kingdom (UK) Dobermanns. We hypothesized that the TTN and PDK4 gene variants would not be associated with DCM in UK Dobermanns and that there would be an association between the RNF207 mutation and DCM. We included 74 client owned dogs (30 control dogs and 44 dogs with DCM) in the study. Allele frequencies for each variant were calculated. Chi-square testing was used to assess for differences in allele frequencies and genotype proportions between groups. Overall allele frequency in this cohort was 35% for the TTN variant, 18% for the PDK4 variant, and 37% for the RNF207 variant. There was no difference in allele or genotype frequencies between control and DCM dogs for TTN or PDK4 (p =  0.79 for both allele frequencies, p =  0.91 for TTN and p =  0.78 for PDK4 genotype frequencies). There was a significant difference in the allele frequencies of the RNF207 variant between DCM cases and controls (OR 2.4 (95% CI 1.07 – 5.15), p =  0.03) and genotype frequencies for RNF207, with a homozygous genotype found almost exclusively in DCM dogs (p =  0.034). We conclude that the previously reported RNF207 variant appears associated with DCM in UK Dobermanns, but there was no association with the previously reported TTN or PDK4 mutations. This is important when considering selective breeding in different populations of Dobermanns. However, the small sample size may impact the generalizability of the results.